1975
DOI: 10.1007/bf00584796
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholine receptor: Modification of synaptic gating mechanism after treatment with a disulfide bond reducing agent

Abstract: Reduction of a 'reactive' disulfide bond in the postsyraptic membrane of the frog neuromuscular junction by dithiothreitol (DTT) decreases both the sensitivity of the membrane to applied acetylcholine (ACh) and the amplitude of the single 'shot effect'. Analysis of ACh induced conductance fluctuations in voltage clamped frog endplates indicates that DTT reduces both the amplitude gamma and duration tau of the elementary conductance events. The mean control value of gamma was 18.5-10(-12) omega-1 with no signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
29
1

Year Published

1976
1976
1995
1995

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 24 publications
6
29
1
Order By: Relevance
“…There are two main techniques for studying the opening and closing kinetics of end-plate channels. The first, noise analysis, relies on the existence of spontaneous thermal fluctuations at equilibrium which on average relax back to equilibrium along a characteristic time course (Katz & Miledi, 1972, 1973aAnderson & Stevens, 1973;Ben-Haim, Dreyer & Peper, 1975;Neher & Sakmann, 1975, 1976b (Adams, 1975b;Neher & Sakmann, 1975; see also . Both these techniques lead to the same conclusion -that when only a small fraction of the channels are open the dominant kinetic process is usually a single exponential whose time constant is the mean channel lifetime.…”
Section: Introductionmentioning
confidence: 99%
“…There are two main techniques for studying the opening and closing kinetics of end-plate channels. The first, noise analysis, relies on the existence of spontaneous thermal fluctuations at equilibrium which on average relax back to equilibrium along a characteristic time course (Katz & Miledi, 1972, 1973aAnderson & Stevens, 1973;Ben-Haim, Dreyer & Peper, 1975;Neher & Sakmann, 1975, 1976b (Adams, 1975b;Neher & Sakmann, 1975; see also . Both these techniques lead to the same conclusion -that when only a small fraction of the channels are open the dominant kinetic process is usually a single exponential whose time constant is the mean channel lifetime.…”
Section: Introductionmentioning
confidence: 99%
“…The role of thiol groups has been extensively studied in the nACh receptor. Early receptor binding studies found that disulfide-reducing agents (to break disulfide bonds into their component sulfhydryl groups) decrease acetylcholine receptor binding affinity (Karlin, 1969;Ben-Haim et al, 1975;Barrantes, 1980;Walker et al, 1981). More recent electrophysiological studies have shown that these agents inhibit acetylcholine-evoked responses (Steinacker, 1979;Steinacker and Zuazaga, 1981;Aizenman et al, 1989;Bouzat et al, 1991;Rojas et al, 1991).…”
mentioning
confidence: 99%
“…Since the discovery of acetylcholine (ACh) 'noise' at the frog end-plate (Katz & Miledi, 1970), fluctuation analysis has become a powerful tool in the investigation of ACh action at the molecular level (Katz & Miledi, 1972, 1973a, b, 1975Anderson & Stevens, 1973;Landau & Ben-Haim, 1974; Ben-Haim, Dreyer & Peper, 1975;Colquhoun, Dionne, Steinbach & Stevens, 1975;Neher & Sakmann, 1976a, b;Dreyer Walther & Peper, 1976 We are interested in the properties of ACh receptors that appear early in myogenesis. Muscle cell cultures offer certain advantages for developmental studies.…”
Section: Introductionmentioning
confidence: 99%